2012
DOI: 10.7448/ias.15.6.18398
|View full text |Cite
|
Sign up to set email alerts
|

Observational study on HIV‐1‐infected patients treated with an ARV combination therapy including raltegravir: the RACING cohort results at month 12

Abstract: The French RACING cohort study is a 24-month, observational, longitudinal, prospective, multicenter study on HIV-1 infected patients being treated with an antiretroviral combination therapy containing raltegravir. The objectives of this study are to describe the viro-immunological course, characterize and document adverse events (AEs), describe patient adherence at M6 (month 6) and examine clinical-biological data for patients undergoing ARV therapy including raltegravir at M12 (month 12). Demographic, viro-im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…A total of 34 serious AEs were reported, of which five were possibly or probably related to RAL. In general, a favourable tolerability profile has been demonstrated for RAL since the earlier registration studies, with headache and gastrointestinal complaints representing the most common reported AEs . In contrast, mild neuropsychiatric disorders have been infrequently recorded (usually reported on a subjective basis), and cases of rhabdomyolisis and hypersensitivity reactions have been extremely rare.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 34 serious AEs were reported, of which five were possibly or probably related to RAL. In general, a favourable tolerability profile has been demonstrated for RAL since the earlier registration studies, with headache and gastrointestinal complaints representing the most common reported AEs . In contrast, mild neuropsychiatric disorders have been infrequently recorded (usually reported on a subjective basis), and cases of rhabdomyolisis and hypersensitivity reactions have been extremely rare.…”
Section: Discussionmentioning
confidence: 99%